2007
DOI: 10.1038/sj.ijir.3901567
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of the reliability and validity of the premature ejaculation diagnostic tool

Abstract: This study details the further validation of the Premature Ejaculation Diagnostic Tool (PEDT), a fiveitem tool, developed to systematically apply the Diagnostic and Statistical Manual of Mental Disorders, revised version 4 (DSM-IV-TR), criteria in diagnosing presence or absence of premature ejaculation (PE). A total of 102 men completed the PEDT and were then interviewed by one of the seven clinical experts, who made a diagnosis of presence or absence of PE. The diagnoses from these two methods were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 12 publications
5
68
0
3
Order By: Relevance
“…Therefore, younger men might be more stable in terms of their ejaculatory function and control compared to older men. This is somewhat supported by a study where test-retest reliability of the PEDT (ICC = 0.88) was higher in younger patients compared with older patients [32].…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, younger men might be more stable in terms of their ejaculatory function and control compared to older men. This is somewhat supported by a study where test-retest reliability of the PEDT (ICC = 0.88) was higher in younger patients compared with older patients [32].…”
Section: Discussionsupporting
confidence: 68%
“…The validity of the PEDT in diagnosing PE compared with clinical expert opion has been shown by the same group in another study. 12 In this study we carried out the Turkish validation of the PEDT. The use of factor analysis confirmed that the five-item solution used by Symonds et al is appropriate for use by Turkish men.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the women were partners of men taking part in another study to develop a PE diagnostic tool. 22,23 Men taking part in the validation of the PE diagnostic tool either met the DSM-IV-TR classification for PE and had an intravaginal ejaculatory latency time (IELT) of less than 2 min at least 70% of the time, as measured over 4 weeks using a stopwatch, or they were diagnosed as having PE through a diagnostic interview conducted by a clinical expert. 12 These experts had several years of experience in active diagnosing practice and treating men with PE, and were recognized as thought leaders, published authors or clinical study investigators.…”
Section: Study Populationmentioning
confidence: 99%